(untitled) (Revista Cientifica Ingenio Magno, 2022)
This article aims to design and manufacture a robotic arm with 5 degrees of freedom of free software and hardware, low cost and manufactured mostly by machining and 3D printing processes that allows advanced manufacturing operations such as additive manufacturing through a 3D printing hotend, laser cutting and engraving processes as well as a clamping system for parts. This tool will be designed and manufactured at the Tunja sectional Santo Tomás University, a university in which a rapid prototyping tool is necessary for the academic activities of teachers and students since there is currently no one mainly due to its high cost in the market. . This robotic arm seeks to improve learning processes, integrating the student into an automated manufacturing environment using CNC machines, designing and manufacturing complex parts on this type of machine with a significant impact on learning and teaching this type of technology